Basic boundary-value problems for one equation with fractional derivatives
We prove some properties of solutions of an equation ^2αux_1^2α + ^2αux_2^2α + ^2αux_3^2α = 0, α ( 12 ; 1 ], in a domain Ω R^3 which are similar to the properties of harmonic functions. By using the potential method, we investigate principal boundary-value problems for this equation., number=1, journal=Ukrains’kyi Matematychnyi Zhurnal, author=Lopushanskaya, G. P., year=1999, month=Jan., pages=48–59